Serological study of brucellosis and leptospirosis in equines of island Maiandeua (Algodoal) state of Para - Vilhena Beckman Pinho, Ana Paula; Santos Kuroda, Rosely Bianca; Vasconcellos, Silvio Arruda; Ferreira Neto, Jose Soares; Ossada, Raul; Feijo de Souza, Vanessa Aparecida; Rocha, Katarine de Souza; Paz, Giselle Souza da [UNESP]; Guimaraes de Moraes, Carla Cristina (Univ Estadual Londrina, 2015)
The aim of this study was to study the seroepidemiological profile of brucellosis and leptospirosis in horses traction Island Maiandeua, state of Para. In two distinct periods, blood samples were collected from 52 animals of both sexes and different ages (2 to 17 years), totaling 104 samples. For the research of antibodies anti-Brucella abortus were used in rapid agglutination test in plate. In the first harvest, none animal was positive, however in the second harvest there were three animals reactive serum. The research of antibodies anti-Leptospira spp. was performed with the use of the microscopic agglutination test (MAT), the first harvest was 23.07% reacting animals and 15.38% at the second harvest, for one or more Leptospira spp. with titers ranging from 100 to 200. The predominant serotype at first and second harvest was the Autumnalis 40% and 37.5% respectively. According to age, it was observed in group 1 (2 to 7 years) 27.78% and 13.89% respectively in the two samples and the second group (> 7 years) was found 12.50% and 18 75% of reactive serum. The results observed in this study demonstrated that the island of Maiandeua, state of Para, there is the presence of Leptospira spp, with the most frequent serovar autumnalis and possible exposure of animals to brucella smooth, suggesting low risk of infection in the population of horses examined.

O objetivo do estudo foi avaliar o perfil soroepidemiológico da brucelose e leptospirose em equídeos de tração da ilha de Maiandeua, estado do Pará. Em dois períodos distintos, foram colhidas amostras sanguíneas de 52 animais, de ambos os sexos e diferentes idades (2 a 17 anos), totalizando 104 amostras. Para a pesquisa de anticorpo anti-Brucella lisa foi utilizado o teste de soroaglutinação rápida em placa. Na primeira colheita, nenhum animal foi reagente, entretanto na segunda colheita houve três animais sororeagentes. A pesquisa de anticorpos anti-Leptospira spp. foi efetuada com o emprego da técnica de soroaglutinação microscópica (SAM), na primeira colheita houve 23,07% animais reagentes e 15,38% na segunda colheita, para um ou mais sorovares de Leptospira spp. com títulos variando de 100 a 200. O sorovar predominante na primeira e segunda colheita foi o Autumnalis com 40% e 37,5% respectivamente. De acordo com a idade, observou-se no grupo 1 (2 a 7 anos) 27,78% e 13,89% nas duas colheitas respectivamente e no grupo 2 (> 7 anos) encontrou-se 12,50% e 18,75% de sororeagentes. Os resultados observados no presente estudo demonstraram que na ilha de Maiandeua, estado do Pará, existe a presença de infecção por Leptospira spp, com o sorovar Autumnalis, o mais frequente, e possível exposição dos animais a Brucela lisa, sugerindo risco baixo de infecção na população de equinos examinada.
Keywords: Brucellosis; lEptospirosis; Equine; Island Maiandeua; Algodoal; Brucelose; Leptospirose; Equídeos; Ilha de Maiandeua; Algodoal